Utilization of jackfruit pulp (Artocarpus heterophyllus L.) in nata production. - Cansancio, Jeremie Joy P.
This study focused on the utilization of jackfruit pulp (Artocarpus heterophyllus l.) as a raw material in the production of nata. There were four fermentation periods (8, 10, 12, and 14 days) and nata formed in these periods subjected to physico-chemical analysis. Physico-chemical analysis showed that the TSS of jackfruit pulp was 33.33°B, pH of 5.41, titratable acidity of 0.175% and moisture content of 65.67%. Using One-way ANOVA at 5% significance level, it was determined that physico-chemical properties of nata have a significant difference with fermentation time at P-value < 0.05. Correlation analysis showed that TSS, TA, and texture of nata have a strong linear relationship with the yield whereas pH and moisture content showed a strong negative linear relationship. JF8, JF10, JF12, and JF14 generated a yield of 9.36%, 16.21%, 18.63%, and 21.0% respectively. JF14 or nata produced after 14-day fermentation period was selected as the best nata yield (BNY). The product as evaluated to have a pH 3.79, 98.78% moisture content, TSS of 2.0, TA of 1.97% and hardness value of 1.455N. Sensory evaluation results showed that BNY had a translucent white color and was described as moderately soft and moderately smooth. Moreover, it was evaluated as like extremely by the children, youth, and adult group.